New insights into the key role of HIF-1α in IL-10-producing B cells - Meng, Xianyi; Bozec, Aline (Cell Stress, 2018)
Hypoxia-inducible factors (HIFs) are essential transcription factors for the cellular response to hypoxia. Expression and stabilization of HIFs can be triggered by hypoxia or by other factors under pathological stress such as inflammation and infection. Indeed, regulatory function of HIFs has been implicated in a variety of different immune cells like macrophages and T cells. In our recent study, we delineated HIF-1α and HIF-2α roles in B cells (Nat Commun, 9:251). We demonstrated that lack of HIF-1α in B cells leads to impaired IL-10-producing CD1dhiCD5+ B cells expansion by modulating their glycolytic metabolism. We identified HIF-1α as a critical transcriptional factor involved in IL-10 production by B cells, thereby influencing the course of autoimmune diseases.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Autoimmune disease; B cells; Glycolysis; HIF-1α; IL-10; Metabolism